Glycochenodeoxycholate induces cell survival and chemoresistance via phosphorylation of STAT3 at Ser727 site in HCC. Issue 3 (9th September 2019) - Wang, Jue; Zhou, Maojun; Jin, Xin; Li, Bingxin; Wang, Chengzhi; Zhang, Qi; Liao, Mingmei; Hu, Xuan; Yang, Manyi
Abstract: Glycochenodeoxycholate (GCDA) is closely associated with carcinogenesis and chemoresistance of hepatocellular carcinoma (HCC). Signal transducer and activator of transcription 3 (STAT3), a transcription factor, is involved in various human tumors. Whether GCDA induces chemoresistance through STAT3 and the mechanism of action remains elusive. In this study, we firstly found that the expression level of STAT3 has a positive correlation with chemoresistance of HCC cells. Moreover, GCDA can upregulate the expression of STAT3 protein. Hence, we suspect that GCDA may induce chemoresistance of HCC cells via STAT3. Mechanistically, GCDA stimulates phosphorylation of STAT3 at Ser727 site and mediates pSer727‐STAT3 protein to translocate and aggregate in the nucleus, which is important for cell survival. When Ser727 of STAT3 mutated to Asp, the capacity of STAT3 to accumulate in the nucleus was attenuated, STAT3‐induced cell survival was impaired and GCDA‐induced chemoresistance was abolished. In addition, while activation of extracellular signal‐regulated kinase 1/2 (ERK1/2) was inhibited by PD98059, phosphorylation of STAT3 at Ser727 induced by GCDA was suppressed. Taken together, these data demonstrate that GCDA‐enhanced survival of liver cancer cells may occur through the activation of STAT3 by phosphorylation at Ser727 site via mitogen‐activated protein kinase/ERK1/2 pathway, which may contribute to the progression of human liver cancer and chemoresistance. Abstract : We firstly found that the expression level of signal transducer and activator of transcription 3 (STAT3) has a positive correlation with chemoresistance of hepatocellular carcinoma (HCC) cells. Following data demonstrate that glycochenodeoxycholate (GCDA) promotes survival and chemoresistance of human liver cancer cells by activating the anti‐apoptotic function of STAT3 via phosphorylation at Ser727 residue through MAPK/ERK1/2 pathway, which is a noncanonical mechanism. GCDA‐induced STAT3 phosphorylation at Ser727 site (but not canonical Tyr705 site) and the nuclear translocation and aggregation of pSer727‐STAT3 protein lead to the long‐term survival function and chemoresistance of human liver cancer cells.